Azoarenes with Opposite Chiral Configurations: Light‐Driven Reversible Handedness Inversion in Self‐Organized Helical Superstructures1. Issue 34 (20th June 2013) - Li, Yannian; Wang, Mengfei; White, Timothy J.; Bunning, Timothy J.; Li, Quan
<x xml:space="preserve">Abstract</x> On the other hand: Azoarene compounds with axially chiral binaphthyl units of the same and opposite chiral configurations were doped into achiral liquid crystals (LCs). They were found to efficiently induce self‐organized helical superstructures, which could be reversibly tuned by light irradiation using trans–cis photoisomerization to change the handedness of the helix (see scheme) in LC hosts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>